Flexible systems and their effectiveness in designing interior spaces(Private university buildings as a model) - Abdel-Zahra Odeh Hassan; Rajaa Saadi Lafta (الاكاديمي)
The idea and philosophy of flexible systems and their effectiveness in the field of interior design came as one of the important influential points to confront future developments and to lay the foundations for achieving all functional and aesthetic requirements through the possibility of change, and the university system is one of the systems most affected by these changes. Through the preliminary exploratory study of such spaces, it was revealed that there is no identification of the influence of context. The functional and spatial pattern of these buildings depends on the degree of influence of these characteristics. Also, previous studies did not provide a clear definition of the characteristics that are most exciting in the flexibility of buildings in a way that meets the designer’s need for use in future designs and the possibility of evaluating the flexibility of building spaces from their initial plans. Due to the lack of a unified and effective flexible design system in university buildings, the research problem was defined through the following question: What is Applications of flexible systems and how effective are they in achieving the principles of design flexibility in designing the interior spaces of university buildings?